The Oxford handbook of the Book of Revelation - Koester, Craig R. ([Oxford handbooks], 2020)
Introduction to Revelation's social setting, theological perspective, and literary design /Craig R. Koester --pt. 1: Literary features of the book of Revelation --The genre of the book of Revelation /Mitchell G. Reddish --Narrative features of the book of Revelation /James L. Resseguie --Imagery in the book of Revelation /Konrad Huber --Rhetorical features of the book of Revelation /David A. deSilva --The Old Testament in the book of Revelation /Steve Moyise --Revelation's use of the Greek language /David L. Mathewson --The hymns in Revelation /Justin P. Jeffcoat Schedtler --pt. 2: Social setting --Revelation and Roman rule in first-century Asia Minor /Warren Carter --Relationships among Christ-believers and Jewish communities in first=century Asia Minor /Mikael Tellbe --Greco-Roman religions and the context of the book of Revelation /Richard S. Ascough --John's apocalypse in relation to Johannine, Pauline, and other forms of Christianity in Asia Minor /Paul Trebilco --pt. 3: Theology and ethics --God in the book of Revelation /Martin Karrer --Jesus in the book of Revelation /Loren L. Johns --The spirit in the book of Revelation /John Christopher Thomas --Creation and new creation in the book of Revelation /Mark B. Stephens --Perspectives on evil in the book of Revelation /Gregory Stevenson --Violence in the Apocalypse of John /David L. Barr --The city-women Babylon and New Jerusalem in Revelation /Lynn R. Huber --The people of God in the book of Revelation /Peter S. Perry --pt. 4: History of reception and influence --The Greek text of Revelation /Juan Hernández Jr. --Revelation and the New Testament Canon /Tobias Nicklas --Reception history and the interpretation of Revelation /Ian Boxall --The interpretation of the book of Revelation in early Christianity /Charles E. Hill --The interpretation of John's apocalypse in the Medieval period /Julia Eva Wannenmacher --The book of Revelation in music and liturgy /Paul Westermeyer --Forms of futuristic interpretation of Revelation in the Modern period /Joshua T. Searle with Kenneth G. C. Newport --pt. 5: Currents in interpretation --Feminist interpretation of Revelation /Susan E. Hylen --Interpreting Revelation through African American cultural studies /Thomas B. Slater --Post-colonial interpretation of the book of Revelation /Harry O. Maier.